Kestabilan Model Epidemi Seir dengan Matriks Hurwitz - Roni Tri Putra; Sukatik - -; Sri Nita - (Jurnal Ilmiah Poli Rekayasa, 2016)
In this paper, it will be studied local stability of equilibrium points of  a SEIR epidemic model with infectious force in latent, infected and immune period. From the model it will be found investigated the existence and its stability of points its equilibrium by Hurwitz matrices. The local stability of equilibrium points is depending on the value of the basic reproduction number  If   the disease free equilibrium is local asymptotically stable.